Exploring the Relations between Civic Identity and Character Attributes in Young Adult Men. - Tirrell, Jonathan. (2017)
Abstract: Having good character guides individuals to pursue positive goals, to do the right thing, and to think and act in prosocial ways. In order to function in such prosocial ways, one must also have a sense of self, or identity, that prioritizes prosocial attitudes and behaviors over self-serving ideas and interests. This sense of self in relation to society has been termed civic identity. This research explored the relations between civic identity and character among 865 men (Mage = 19.84 years, SD = 1.86) from four post-secondary schools in Pennsylvania. Results indicated significant relations between civic identity and general character, diligence, and helping behaviors. Results also indicated that helping behaviors were a significantly better predictor of civic identity than were diligence and general character. Implications for future studies of helping behaviors as a component of civic identity and character development are discussed.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of Child Study and Human Development.; Advisor: Richard Lerner.; Committee: Sara Johnson, and Jacqueline Lerner.; Keywords: Developmental psychology, and Social psychology.